Гидрологические и гидрохимические характеристики участков болотных лесов у оз. Нижнее Падозеро (Карелия) : HYDROLOGICAL AND HYDROCHEMICAL CHARACTERISTICS OF FORESTED MIRE SITES IN THE VICINITY OF LAKE PADOZERO(KARELIA, RUSSIA) - Кутенков С.А. (Труды Института биологии внутренних вод РАН, 2017)
При помощи градиентного анализа исследована связь напочвенного растительного покрова болотных лесов с рядом гидрохимических показателей, сомкнутостью древостоя и глубиной торфа. Показано, что ведущий растительный градиент связан с трофностью и в наибольшей степени коррелирует с показателями pH, Eh, концентрацией растворённого кислорода, активностью ионов кальция (pCa) и сомкнутостью древостоев. Второй градиент связан с различными типами водно-минерального питания, с ним средне коррелирует глубина торфа, температура и pH. При помощи самописцев получен ход уровня болотно-грунтовых вод на трёх участках с различной растительностью. Проведено построение простой имитационной модели уровня вод, оценены основные составляющие гидрологического бюджета участков. Наибольшие значения реакции уровня на выпадающие осадки, расчётного испарения и стока получены для ельника таволгового, занимающего окрайковое положение на болотном массиве. : The relationships between the groundcover vegetation and the site characteristics (hydrochemical parameters, density of tree stands canopy and peat depth) were examined by gradient analysis (NMS) based on the 79 sample plots of forested mires at Lake Padozero (Karelia, Russia). It is demonstrated that the leading gradient of vegetation is associated with the trophic status and is most correlated with pH, Eh, concentration of dissolved oxygen, activity of calcium ions (pCa) and density of stands canopy. The second gradient is associated with different types of water-mineral nutrition and has a medium correlation with the peat depth, temperature and pH. Leveloggers were used to record the dynamics of water level in three sites of forested mires with different vegetation. A simple simulation model of water table variability has been build up; the main compounds of the hydrological budget have been estimated. The highest values of the water level response to precipitation, potential evapotranspiration and runoff are obtained for the spruce site at the margin of mire massif.